Осы-блестянки рода Brugmoia (Hymenoptera, Chrysididae) Тянь-Шаня и сопредельных территорий - Тарбинский, Ю.С. (Вестник зоологии, 2000)
Приводится характеристика рода Brugmoia Radoszkowski, определительная таблица для 5 видов, обнаруженных на исследуемой территории. Описаны 3 новых вида: B. silaphila sp. n. сходна с B. pellucida Rad. ярко-зеленой окраской, отличаясь более крупными размерами и окрашенным анальным краем брюшка; B. kyrgyzica sp. n. сходна с B. eoa Semenov из Ирана, отличаясь окраской тела; B. arenaria sp. n. отличается от всех известных видов сине-фиолетовым цветом всего тела, правильно расставленными многочисленными длинными шипами, окрашенными одинаково с третьим тергитом. The genus Brugmoia Radoszkowski is characterised, and a key to 5 species known to occur in the Tien Shan mountains and adjacent territories is given. 3 new species are described: B. silaphila sp. n. fits near B. pellucida Rad. in brightly green body colouration, differing by larger size and darkened anal margin of abdomen; B. kyrgyzica sp. n. is similar to B. eoa Semenov from Iran, differing by body colouration; B. arenaria sp. n. differs from all the known species by bluish-purple colour of all the body, regularly placed numerous long teeth concolorous with the 3rd tergite.